2004
DOI: 10.1007/s00441-004-0959-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted type V collagen fibrils as cementing materials in the formation of cell clumps in culture

Abstract: Previous studies have reported that type V collagen is an anti-adhesive substrate for cultured cells in that the cells detach from culture dishes coated with type V collagen molecules or polypeptides derived from them. We have noticed that human fetal lung fibroblasts (TIG-1) initially show no reduction in adherence to and spreading on a dish coated with reconstituted type V collagen fibrils but eventually detach from the dish and form cell clumps. To determine the way in which reconstituted type V collagen fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…Col. V with high concentration can make L929 fall off the culture medium and gather into clusters ( Fig. 11 ), similar to the Takanori’s result [ 33 ]. With an increase in the Col. V proportion, the diameter of collagen fibers was changed, which further affected the combination of collagen with cells.…”
Section: Discussionsupporting
confidence: 80%
“…Col. V with high concentration can make L929 fall off the culture medium and gather into clusters ( Fig. 11 ), similar to the Takanori’s result [ 33 ]. With an increase in the Col. V proportion, the diameter of collagen fibers was changed, which further affected the combination of collagen with cells.…”
Section: Discussionsupporting
confidence: 80%
“…In response to the collagens, the cells are modulated in their proliferation and expression of matrix metalloproteinases (MMPs) (Kerkvliet et al, 2003). Of the collagens tested it was in particular collagen V that appeared to affect fibroblast behavior (Fukuda et al, 1988;Hatai et al, 1993;Kerkvliet et al, 2003;Kihara et al, 2004;Luparello et al, 1990;Ruggiero et al, 1994Ruggiero et al, , 1996Sakata et al, 1992Sakata et al, , 1994Yamamoto et al, 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Most studies focusing on the effects of the different collagen types in relation to cell activity made use of monolayer cultures (Kerkvliet et al, 2003;Kihara et al, 2004;Ruggiero et al, 1994Ruggiero et al, , 1996. In order to approximate the in vivo situation, fibroblasts are seeded in a 3D collagen matrix in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The type Vp collagen prevents the attachment, spreading [31], and proliferation [32] of endothelial cells and of porcine vascular smooth muscle cells in vitro [33]. Kihara et al [34,35] have shown that the reconstituted fibrils from pepsin-extracted type V collagen subtype with the chain composition of [α1(V)] 2 α2(V) (Vp112) strongly adhere to the surface of cultured fibroblasts and form the clump aggregates consisting of cells and type Vp112 collagen fibrils. This effect is not shared with type I collagen, indicating that the reconstituted fibrils from the triple-helical domain of type V collagen have a different property compared to those of type I collagen.…”
Section: Introductionmentioning
confidence: 98%